Managing forest plantation for suitable water resources. (April 2019) - Basuki, T M
Extended Abstract: Controversial debate on the impact of forest plantation has been going on for several decades. Some researchers have examined reduction on water yield because of the expansion of plantation forest areas along with the increase in ages [1-3]. On the contrary, forests have been recognized to provide a positive effect on ecosystem functions and services in watersheds [4] and to mitigate the negative impacts of climate change [5]. Regarding these two opinions, which consider that forests reduce water yield and forests provide benefits for environmental, Ellison et al. [6] have tried to classify into demand and supply sides. The first group which is the 'demand side', consider that either trees or forests use the existing water and they cause a lack of available water for downstream areas [6]. The second group which is the 'supply side' believes that forest has essential roles in the water cycle, and consider increasing forest cover will improve environmental condition including increasing water resources [6]. Due to different opinions about the effect of forests on environmental, especially water yield, therefore some research findings from the previously published papers are presented in this paper. The aim of the paper is to present research findings of some characteristics of water yield from forest plantation including teak and pine catchments and to provide some considerations for sustainable water resources in forest plantation watersheds. A previous study conducted by [7] in Loess Plateau-China found that planted 80% of the treated catchment reduced 32% of water yield compared to natural grassland. Although the forest plantation reduced water yield, however, it reduced the volume and peak flow of storm runoff events [7]. [1] also in China observed that afforestation at the semi-arid, northern China, decreased 50mm/year (50%) of water yield and 300 mm/year (30%) of water yield in the tropical (southern) region. In South Africa, [8] examined that conversion of grassland (annual runoff of 236 mm) into eucalypts in the entire catchment causes a significant decrease in streamflow in the third year after planting and the stream dried up completely in the ninth year after planting. Afforestation of grassland (annual runoff of 217 mm) with pines of an entire catchment causes a significant decrease in streamflow in the fourth year after planting and the stream to dry up completely in the twelfth year after planting. In Indonesia, [9] conducted research on the impact of various old teak plantation based on catchments measurements. The research finding showed that the higher the teak areas, the lower the annual water yield [9]. The analysis was based on data from 2008 to 2015 [9]. At the same study areas, the trendline showed that the higher the old teak coverage areas the higher the low flow. The decrease in annual water yield with the increase in forest plantation was also found by [10] in a pine plantation. Similar to [7], [11] also found that the pine plantations can reduce peak flow until a certain level of a rainfall event. For rainfall <70 mm/event, there was a trend line indicated that the increase in pine plantation areas will decrease the peak flow [11]. For rainfall >70 mm/event, however, the trendline showed a horizontal shape which showed that the peak flow at the catchment covered by pine plantation area of 40 % until 95% are almost similar [11]. At the same catchments covered by various pine plantation areas, research findings of [11] showed that at daily rainfall >70mm, a positive correlation trend between rainfall and base flow was observed. At daily rainfall 40 -70 mm, the trend lines between rainfall and base flow were horizontal and for daily rainfall <40 mm, most of the graphics showed negative correlation [12].